Synchronous endocrine tumors of small intestine: Report of a case - Nilay ŞEN; Neşe ÇALLI DEMİRKAN and Ayşegül AKSOY ALTINBOĞA and Hacı BOLAT and Ergün ERDEM (Turkish Journal of Gastroenterology, 2019)
-